2016
DOI: 10.1111/jssr.12283
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance Behavior Following Terror Event Exposure: Effects of Perceived Life Threat and Jewish Religious Coping

Abstract: The current research was designed to examine associations of perceived life threat (PLT) and religious coping with the development of avoidance behavior following terror event exposure. Based upon the terror management theory (TMT), we hypothesized that religious coping, through its effect on religious beliefs as a meaning system, would moderate the impact of threat, as expressed in PLT, on an individual's reaction to terror event exposure, as manifested in avoidance behavior. Participants were 591 Israeli Jew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…Consistent pattern of associations was found in the case of negative religious coping and symptoms of disorders: depression (Ahrens et al, ; Henslee et al, ; Leaman & Gee, ), PTSD (Berzengi, Berzenji, Kadim, Mustafa, & Jobson, ; Cuevas et al, ; Currier et al, ; Gerber et al, ; Harris et al, ; Leaman & Gee, ; McCann & Webb, ; Park et al, ; Raines et al, ; Wortmann et al, ; Zukerman, Korn, & Fostick, —only in women; Zukerman, Korn, Shapiro, & Fostick, , avoidance symptoms), distress (Chan & Rhodes, ), suicidal ideations (Currier, Smith, & Kuhlman, ; Kopacz et al, ; Raines et al, ), and substance use (Raines et al, ). Lack of significant associations between the negative coping and symptoms of PTSD was demonstrated in Ahrens et al (), Al‐Hadethe et al (), and Chan and Rhodes ().…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent pattern of associations was found in the case of negative religious coping and symptoms of disorders: depression (Ahrens et al, ; Henslee et al, ; Leaman & Gee, ), PTSD (Berzengi, Berzenji, Kadim, Mustafa, & Jobson, ; Cuevas et al, ; Currier et al, ; Gerber et al, ; Harris et al, ; Leaman & Gee, ; McCann & Webb, ; Park et al, ; Raines et al, ; Wortmann et al, ; Zukerman, Korn, & Fostick, —only in women; Zukerman, Korn, Shapiro, & Fostick, , avoidance symptoms), distress (Chan & Rhodes, ), suicidal ideations (Currier, Smith, & Kuhlman, ; Kopacz et al, ; Raines et al, ), and substance use (Raines et al, ). Lack of significant associations between the negative coping and symptoms of PTSD was demonstrated in Ahrens et al (), Al‐Hadethe et al (), and Chan and Rhodes ().…”
Section: Resultsmentioning
confidence: 68%
“…It is, therefore, not clear whether nonreligious individuals experience negative religious coping/religious strain. Zukerman et al () reported that nonreligious participants actually demonstrated higher levels of negative religious coping and intrapersonal religious coping. Relatively high levels of negative religious coping were also found among nonreligious participants in Zukerman and Korn ().…”
Section: Resultsmentioning
confidence: 99%
“…Several research findings suggest that being religious may have a protective effect for individuals exposed to terrorism ( Levav et al, 2008 ; Casakin and Billig, 2009 ; Korn and Zukerman, 2011 ; Zukerman and Korn, 2014 ; Zukerman et al, 2016 , 2017 ). For example, students who define themselves as secular reported higher rates of avoidance behavior following terror event exposure ( Zukerman et al, 2016 ). The reasons behind this variability in response to terror are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that religiosity may moderate the effects of trauma through cognitive schemas; religious cognitive schemas have been found to affect one’s “world assumption”- the basic perception of the world and self ( Janoff-Bulman, 1989 )-and may do so by creating a “protective shield” that prevents negative effects resulting from undergoing an extremely negative experience ( Zukerman and Korn, 2014 ). Indeed, religious coping, conceptualized as drawing upon religious beliefs and practices in order to understand and deal with life stressors ( Pargament, 1997 ), has been suggested as a key factor influencing adaptation after trauma exposure ( Laufer and Solomon, 2011 ; Zukerman et al, 2016 , 2017 ); it can manifest as either positive or negative. Positive religious coping, including benevolent religious appraisal, praying, and seeking spiritual support and connection with G-d, has been associated with better adjustment to stressful events and reductions in post-traumatic stress symptomatology ( Pargament et al, 2000 ; Harris et al, 2008 ; Chan and Rhodes, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation